CONCEPTUAL METONYMY IN PRESIDENT PRABOWO’S FLOOD DISASTER SPEECH - Idawati Situmorang; Mulyadi Mulyadi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study analyzes conceptual metonymy in the President’s speech during the flood disaster inspection in Bener Meriah Regency. The study focuses on metonymy within the Thing and Part Configuration of the Idealized Cognitive Model (ICM) proposed by Kövecses (1998), which includes the relations of whole-for-part and part-for-whole metonymy. Using qualitative discourse analysis, the study examined a 380-word official transcript of President Prabowo’s speech. Data collection employed documentation and indirect observation techniques, supported by audiovisual validation. Data analysis followed the framework proposed by Miles, Huberman, and Saldaña (2014), which consists of data reduction, data display, and conclusion drawing. Findings show that whole-for-part metonymy dominates, while part-for-whole occurs less frequently. The dominance of whole-for-part metonymy reflects a discourse strategy that emphasizes institutional responsibility and collective solidarity in crisis contexts. By employing this strategy, the President legitimizes state presence and authority while guiding public perception of disaster management. In this way, the study demonstrates that metonymy simplifies institutional realities, constructs collective responsibility, and facilitates public understanding in crisis communication. This research contributes to cognitive semantics and political discourse studies by highlighting metonymy’s role in crisis communication.